2011
DOI: 10.1186/cc10046
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in critical ill patients affected by influenza A (H1N1) virus infection

Abstract: IntroductionLittle information exists about the impact of acute kidney injury (AKI) in critically ill patients with the pandemic 2009 influenza A (H1N1) virus infection.MethodsWe conducted a prospective, observational, multicenter study in 148 Spanish intensive care units (ICUs). Patients with chronic renal failure were excluded. AKI was defined according to Acute Kidney Injury Network (AKIN) criteria.ResultsA total of 661 patients were analyzed. One hundred eighteen (17.7%) patients developed AKI; of these, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 33 publications
6
37
1
7
Order By: Relevance
“…Severe sepsis, often complicated by renal hypoperfusion in septic shock, is characterized by a profound inflammatory milieu and associated dysfunction of multiple organ systems. Rates of AKI reported in septic patients range from 13% up to >64.4% [4951, 87, 108, 109]. The toxic effects of sepsis on AKI do not appear to be specific to bacterial or fungal pathogens.…”
Section: Special Patient Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Severe sepsis, often complicated by renal hypoperfusion in septic shock, is characterized by a profound inflammatory milieu and associated dysfunction of multiple organ systems. Rates of AKI reported in septic patients range from 13% up to >64.4% [4951, 87, 108, 109]. The toxic effects of sepsis on AKI do not appear to be specific to bacterial or fungal pathogens.…”
Section: Special Patient Populationsmentioning
confidence: 99%
“…The toxic effects of sepsis on AKI do not appear to be specific to bacterial or fungal pathogens. The 2009 H1N1 influenza pandemic demonstrated that viral infections caused significant rates of AKI (up to 51%) sometimes exceeding those seen in more common infections [4953]. Of note, delays in the administration of appropriate antibiotics are associated with the highest incidence of sepsis-induced AKI.…”
Section: Special Patient Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies, however, were limited by design (case reports [14,17,20,22,24,28] or small case series [13,15,18,21,27]), small sample size [16,19,25], or single-center enrollment [13,15,16,18,21]. There have been few larger scale prospective multi-center cohorts [19,23,26], none of which described the Canadian pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction pH1N1 (2009 pandemic influenza A) presented with substantial pulmonary involvement; however, extrapulmonary complications were not uncommon and represented an additional contribution to mortality [1][2][3]. Risk factors for poor outcome included multiple-organ dysfunction syndrome and requirement of mechanical ventilation or renal replacement therapies [4][5][6]; indeed, stage III acute kidney injury (AKI) has proved to be an independent risk factor for mortality [7].…”
mentioning
confidence: 99%